Vehicular ad-hoc networks for smart cities : second International Workshop, 2016 - Laouiti, Anis; Qayyum, Amir; Mohamad Naufal Mohamad Saad (Advances in intelligent systems and computing ;, 2017)
This book presents selected articles from the Second International Workshop on Vehicular Adhoc Networks for Smart Cities, 2016 (IWVSC'2016). In order to promote further research activities and challenges, it highlights recent developments in vehicular networking technologies and their role in future smart cities.